Pollen counts in sediment core SF-10 obtained along the coastal plain of Babitonga Bay-Santa Catarina-Brazil - Marcelo Cancela Lisboa Cohen; Neuza Fontes; Érika do Socorro Ferreira Rodrigues; Luiz C R Pessenda; Marlon França; Ed Garret; Junghyung Ryu (PANGAEA, 2025)
Fieldwork was conducted in August 2017 to sample sediment cores. The sediment cores were subsampled (1 cm^3) at 5 cm intervals, resulting in a total of 125 samples that were processed using standard pollen analytical techniques, including acetolysis (Faegri and Iversen, 1989).
In: Cohen, MCL et al. (2025): Topographic, vegetation, radiocarbon and stratigraphic data from Babitonga Bay-Santa Catarina-Brazil [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985002